2017
DOI: 10.7554/elife.21510
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the mechanism of the DEAH-box RNA helicase Prp43

Abstract: The DEAH-box helicase Prp43 is a key player in pre-mRNA splicing as well as the maturation of rRNAs. The exact modus operandi of Prp43 and of all other spliceosomal DEAH-box RNA helicases is still elusive. Here, we report crystal structures of Prp43 complexes in different functional states and the analysis of structure-based mutants providing insights into the unwinding and loading mechanism of RNAs. The Prp43•ATP-analog•RNA complex shows the localization of the RNA inside a tunnel formed by the two RecA-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

21
216
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(238 citation statements)
references
References 54 publications
21
216
0
Order By: Relevance
“…The basic features of this mechanism are the same as determined for other members of the DEAH-box family (31,33). These basic features, including a requirement for translocation, probably reflect the presence in DEAH-box proteins of C-terminal domains that surround nucleic acid substrates and are likely important for translocation (33,(43)(44)(45), as well as conserved sequence motifs within the helicase core. While we established this mechanism using principally DNA G4s, analogous RNA constructs were processed by DHX36 with similar rates, indicating that DHX36 likely uses the same mechanism to disrupt DNA and RNA G4s.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The basic features of this mechanism are the same as determined for other members of the DEAH-box family (31,33). These basic features, including a requirement for translocation, probably reflect the presence in DEAH-box proteins of C-terminal domains that surround nucleic acid substrates and are likely important for translocation (33,(43)(44)(45), as well as conserved sequence motifs within the helicase core. While we established this mechanism using principally DNA G4s, analogous RNA constructs were processed by DHX36 with similar rates, indicating that DHX36 likely uses the same mechanism to disrupt DNA and RNA G4s.…”
Section: Discussionmentioning
confidence: 60%
“…With rate-limiting substrate binding, DHX36 can be described as having achieved a limited definition of 'catalytic perfection' for disrupting these G4s, as any further improvements in the rates of first-order steps would not increase the reaction efficiency or the level of specificity (46). The binding rate constants of ~2 × 10 8 M -1 min -1 for tetramolecular G4s and ~1 × 10 9 M -1 min -1 for unimolecular G4s are 2-3 orders of magnitude below the encounter frequency, most likely owing to the complexity of accommodating the 3′ extension within a crevice of the protein that may be only transiently accessible (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent structures of Prp43 from C. thermophilum have provided insight into how DEAH-box proteins load onto ssRNA adjacent to their target structures to initiate unwinding (57). Among other roles, Prp43 is required in the final step of pre-mRNA splicing, where it disrupts base pairing between the U2 snRNP and the intron branch point, releasing the U2, U5, and U6 snRNPs from the lariat intron (5862).…”
Section: Deah-box Proteins As Molecular Winchesmentioning
confidence: 99%
“…Among other roles, Prp43 is required in the final step of pre-mRNA splicing, where it disrupts base pairing between the U2 snRNP and the intron branch point, releasing the U2, U5, and U6 snRNPs from the lariat intron (5862). Like other DEAH-box proteins, Prp43 lacks sequence specificity for RNA substrates, a property that was rationalized from the crystal structure of the enzyme bound to ADP-BeF 3 and U 7 RNA, as the majority of contacts are formed with the sugar-phosphate backbone of the RNA, not the uracil bases (57, 63). A similar structure without RNA showed that large conformational changes in the C-terminal domains, particularly the ratchet-like and OB-fold domains, lead to an opening of the RNA-binding tunnel between D2 and the C-terminal domains (Fig.…”
Section: Deah-box Proteins As Molecular Winchesmentioning
confidence: 99%